Modern Management of Cancer of the Rectum - Longo, Walter E.; Longo, Walter E.; Reddy, Vikram.; Reddy, Vikram.; Audisio, Riccardo A.; Audisio, Riccardo A. (Springer London : Imprint: Springer, 2015)
Since the last edition of this book,  there has been great progress in all matters relating to rectal cancer. This edition is a revision and update of a gradually changing field in which the surgeon, medical oncologist, and radiation oncologist cannot function without the other.   Modern Management of Cancer of the Rectum deals with every aspect of rectal cancer. Its overall view is delivered by an internationally recognized panel of experts, all of whom are leaders in their field. Each chapter reflects  advances in medical oncology and surgical techniques that have changed the management of rectal cancer.   This book will provide practicing surgeons, surgeons in training, oncologists, radiation oncologists, and all others who diagnose and treat this malignancy with up-to-date information that will ultimately allow for the better management of patients. .